The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ptr.7247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artichoke leaf extract supplementation or artichoke juice consumption on lipid profile: A systematic review and dose–response meta‐analysis of randomized controlled trials

Abstract: Accumulating evidence regarding the effect of artichoke on lipid profile is equivocal. We updated a previous meta‐analysis on the effect of artichoke extract supplementation on lipid profile and performed dose–response analysis. We searched PubMed, Scopus, Web of Science, and Cochrane Library from inception to June 2021 using relevant keywords. Papers from identified articles were collected. Two researchers rated the certainty in the estimates using the GRADE approach. Combining 15 effect sizes from 14 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
(161 reference statements)
1
3
0
Order By: Relevance
“…In our study, there is no significant effect of artichoke on HDL-C level. This finding is in agreement with work in (Shahinfar et al, 2021) which demonstrated, that no significant effect of artichoke on HDL-C level, and also with study in (Sahebkar et al, 2018) which reported that no significant alteration in plasma High Density Lipoprotein-Cholesterol by artichoke.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, there is no significant effect of artichoke on HDL-C level. This finding is in agreement with work in (Shahinfar et al, 2021) which demonstrated, that no significant effect of artichoke on HDL-C level, and also with study in (Sahebkar et al, 2018) which reported that no significant alteration in plasma High Density Lipoprotein-Cholesterol by artichoke.…”
Section: Discussionsupporting
confidence: 93%
“…According to existing literature, the consumption of artichoke leaf extract (ALE) may lead to a reduction in cholesterol levels among individuals with hypercholesterolemia (6). Furthermore, it has been observed that ALE exhibits a reduction in the generation of reactive oxygen species, as well as the oxidation of low-density lipoproteins (LDL) and lipid peroxidation (7).This study 's primary purpose is to evaluate the therapeutic efficacy of artichoke in modulating biochemical oxidants, antioxidant enzymes, and liver biomarkers in adult male albino rats with nonalcoholic fatty liver disease.…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia, clinically featured by abnormally high blood lipid concentrations, is frequently associated with atherosclerotic heart disease, including coronary heart disease, stroke, and peripheral artery disease [1][2][3]. Evidence from 1127 population-based studies measuring blood lipids in 102.6 million people aged 18 years and older showed that although there was little change in total cholesterol, or non-HDL lipoprotein cholesterol in the global population from 1980 to 2018, the net effect in low-and middle-income countries, particularly in East and Southeast Asia, increased but declined in high-income western countries, particularly in Northwest Europe, and in Central and Eastern Europe.…”
Section: Introductionmentioning
confidence: 99%